The uraA locus and homologous recombination in Mycobacterium bovis BCG. - Aldovini, A (1993)
Molecular genetic manipulation of mycobacteria would benefit from the isolation of mycobacterial genes that could serve both as genetic markers and as sequences used to target homologous integration of recombinant DNA into the genome. We isolated the Mycobacterium bovis BCG gene encoding orotidine-5'-monophosphate decarboxylase (OMP-DCase) by complementing an Escherichia coli mutant defective in this activity. The BCG OMP-DCase gene (uraA) and the flanking DNA were sequenced. The predicted BCG OMP-DCase protein sequence is closely related to the Myxococcus xanthus OMP-DCase and more distantly related to the other known prokaryotic and eukaryotic OMP-DCases. To investigate whether homologous integration can occur in M. bovis BCG, an improved protocol for transformation of BCG was developed and a linear fragment of mycobacterial DNA containing the uraA locus, marked with a kanamycin resistance gene, was introduced into BCG cells by electroporation. The kanamycin-resistant BCG transformants all contained vector DNA integrated into the genome. The marked DNA had integrated into the homologous uraA locus in approximately 20% of the transformants. These results have implications for understanding the role of mycobacterial genes in disease pathogenesis and for the genetic engineering of improved mycobacterial vaccines.